Catalyst for olefin polymerization and method for producing olefin polymer
A catalyst system using a specific carbon material and organoaluminum compound with a transition metal compound addresses the challenge of dispersing carbon materials in polyolefins, achieving high polymerization activity and enhanced properties like thermal conductivity and weather resistance without expensive cocatalysts.
Patent Information
- Application Number
- JP2020180632
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-10-28
AI Technical Summary
Existing methods for dispersing carbon materials in polyolefins for enhancing thermal conductivity, electrical conductivity, and weather resistance are hindered by the difficulty in achieving efficient dispersion and require expensive organoaluminumoxy compounds as cocatalysts.
A catalyst system comprising a specific carbon material and organoaluminum compound, along with a transition metal compound, is used to facilitate efficient dispersion of carbon materials in polyolefins without the need for expensive organoaluminumoxy compounds, leveraging a unique electronic interaction between the carbon material and transition metal compound to enhance polymerization activity.
The catalyst system achieves high polymerization activity and efficient dispersion of carbon materials in olefin polymers, providing improved thermal conductivity, electrical conductivity, and weather resistance without the use of costly cocatalysts.
Smart Images

Figure 0007605612000001 
Figure 0007605612000002 
Figure 0007605612000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an olefin polymerization catalyst and a process for producing an olefin polymer using the olefin polymerization catalyst. [Background technology]
[0002] By blending carbon materials such as graphite, graphene, and carbon nanotubes (CNTs) with polyolefins, it is possible to impart high thermal conductivity, electrical conductivity, and weather resistance to the polyolefins (see, for example, Patent Document 1). However, there is a problem in that it is difficult to disperse these carbon materials in polyolefins.
[0003] In order to improve the dispersibility of carbon materials in polyolefins, methods have been proposed for producing composites of carbon materials and polyolefins by polymerization using a polymerization catalyst in which a metal complex is supported or impregnated on the carbon material (see, for example, Patent Documents 2 to 4). However, all of these methods use expensive organoaluminum oxy compounds such as methylaluminoxane (MAO) as co-catalysts, and there is a demand for reducing the production cost. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-071079 A [Patent Document 2] JP 2006-176601 A [Patent Document 3] JP 2007-161741 A [Patent Document 4] Special Publication No. 2005-506404 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide an olefin polymerization catalyst which shows high polymerization activity without using an expensive organoaluminum oxy compound and is capable of producing an olefin polymer in which a carbon material is efficiently dispersed, and a method for producing an olefin polymer using the olefin polymerization catalyst. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a specific carbon material and a specific organoaluminum compound as a co-catalyst, thereby completing the present invention.
[0007] The olefin polymerization catalyst according to the present invention comprises A carbon material (A) that satisfies the following requirements (AI) and (A-II); An organoaluminum compound (B) represented by the following general formula (BI), A transition metal compound (C) represented by the following general formula (CI): Includes. (AI) The oxygen atom / carbon atom molar ratio in X-ray photoelectron spectroscopy (XPS) is 0.018 or more and 0.400 or less; (A-II) Specific surface area measured by BET multipoint method is 100m 2 / g or more 5000m 2 / g or less; R a m Al(OR b ) n H p X q (BI) [In general formula (BI), R a and R b represents a hydrocarbon group having 1 to 15 carbon atoms, which may be the same or different, X represents a halogen atom, m represents an integer of 1 to 3, n represents an integer of 0 to 2, p represents an integer of 0 to 2, q represents an integer of 0 to 2, and m+n+p+q=3. L m MX n ···(CI) [In the general formula (CI), M is an atom selected from the group consisting of atoms of Groups 3, 4, 5, 6, 7, 8, 9, 10, and 11 of the periodic table, and lanthanide atoms; L is a ligand, and a plurality of L may be the same or different from each other, and a plurality of L may be connected by a substituent in L, but at least one L contains at least one atom selected from the group consisting of boron, nitrogen, oxygen, phosphorus, sulfur, and selenium, m is an integer of 2 or more, n is an integer of 1 to 4 that satisfies the valence of M; X is a leaving group selected from a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, an aluminum-containing group, a conjugated diene derivative group, and a neutral ligand capable of coordinating with a lone electron pair, and when n is 2 or more, multiple Xs may be the same or different from each other and may be bonded to each other to form a ring. Effect of the Invention
[0008] According to the present invention, it is possible to provide an olefin polymerization catalyst which shows high polymerization activity without using an expensive organoaluminum oxy compound and is capable of producing an olefin polymer in which a carbon material is efficiently dispersed, and a method for producing an olefin polymer using the olefin polymerization catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. [Olefin polymerization catalyst] The olefin polymerization catalyst of the present invention comprises A carbon material (A) that satisfies the following requirements (AI) and (A-II); An organoaluminum compound (B) represented by the following general formula (BI), A transition metal compound (C) represented by the following general formula (CI): The present invention is characterized by comprising:
[0010] (AI) The oxygen atom / carbon atom molar ratio in X-ray photoelectron spectroscopy (XPS) is 0.018 or more and 0.400 or less. (A-II) Specific surface area measured by BET multipoint method is 100m 2 / g or more 5000m 2 / g or less.
[0011] R a m Al(OR b ) n H p X q (BI) In the above general formula (BI), R a and R b represents a hydrocarbon group having 1 to 15 carbon atoms, which may be the same or different, X represents a halogen atom, m is an integer of 1 to 3, n is an integer of 0 to 2, p is an integer of 0 to 2, q is an integer of 0 to 2, and m+n+p+q=3.
[0012] L m MX n ···(CI) In the general formula (CI), M represents an atom selected from the group consisting of atoms of Groups 3, 4, 5, 6, 7, 8, 9, 10, and 11 of the periodic table, and lanthanide atoms; L represents a ligand, and a plurality of L may be the same or different from each other, and a plurality of L may be connected by a substituent in L, but at least one L contains at least one atom selected from the group consisting of boron, nitrogen, oxygen, phosphorus, sulfur, and selenium; and m is 2 or more. n is an integer of 1 to 4 satisfying the valence of M; X is a leaving group selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, halogen-containing groups, silicon-containing groups, oxygen-containing groups, sulfur-containing groups, nitrogen-containing groups, phosphorus-containing groups, boron-containing groups, aluminum-containing groups, conjugated diene derivative groups, and neutral ligands capable of coordinating with lone electron pairs; when n is 2 or more, multiple Xs may be the same or different and may be bonded to each other to form a ring.
[0013] Each component constituting the olefin polymerization catalyst of the present invention will be described below. <Carbon material (A)> The carbon material (A) used in the present invention satisfies the following requirements (AI) and (A-II).
[0014] (AI) The molar ratio of oxygen atoms to carbon atoms as measured by X-ray photoelectron spectroscopy (XPS) is 0.018 or more and 0.400 or less, preferably 0.020 or more and 0.250 or less, and more preferably 0.022 or more and 0.200 or less.
[0015] The oxygen atom / carbon atom molar ratio is a value obtained by X-ray photoelectron spectroscopy (XPS) measurement, and specifically, the oxygen atom / carbon atom molar ratio is calculated from the peak areas of oxygen atoms and carbon atoms in the spectrum obtained from the carbon material (A).
[0016] The higher the oxygen atom / carbon atom molar ratio, the more preferable it is because the amount of oxygen atoms that can come into contact with the organoaluminum compound (B) described later increases. However, if the oxygen atom / carbon atom molar ratio is too high, the sp 2 The two-dimensional sheet structure due to bonded carbon tends to decrease.
[0017] The oxygen atoms in the carbon material (A) may be formed by substituting some of the carbon atoms in the carbon material with oxygen atoms, may be contained in a substituent on the carbon material, or may be contained in a compound coordinated to or adsorbed on the surface or pores of the carbon material.
[0018] The amount of oxygen atoms in the carbon material (A) can be controlled by the production conditions of the carbon material, heat treatment (e.g., drying, calcination), water absorption treatment, surface modification or modification treatment (e.g., introduction of functional groups, oxidation treatment, reduction treatment), etc.
[0019] (A-II) Specific surface area measured by BET multipoint method is 100m 2 / g or more 5000m 2 / g or less, preferably 150m 2 / g or more 3000m2 / g or less, more preferably 200m 2 / g or more 2000m 2 / g or less.
[0020] The specific surface area is a value obtained by the BET (Brunauer-Emmett-Teller) multipoint method using an adsorption isotherm. Specifically, the adsorption isotherm of a carbon material (A) that has been subjected to a vacuum heating degassing treatment at 50°C or higher and 300°C or lower is measured using nitrogen gas as an adsorbate, a BET plot is created from the adsorption isotherm, and the monomolecular adsorption amount is calculated from the slope and intercept of the plot to obtain the specific surface area.
[0021] When a carbon material (A) having fine pores is used, if the specific surface area is too high, the pore size becomes small (in other words, the proportion of micropores increases), and contact with the organoaluminum compound (B) and the transition metal compound (C) described below is inhibited. In the case of a carbon material (A) having fine pores, the pore volume is preferably 0.1 to 5.0 cm 3 / g, more preferably 0.3 to 4.0 cm 3 / g.
[0022] The specific surface area of the carbon material (A) can be controlled by the raw material, size (nano-sizing), shape, and pores of the carbon material, and methods for forming pores include a method of introducing a template source as exemplified in JP2020-093977A and a method using an activation treatment.
[0023] The carbon material (A) used in the present invention is a solid carbon material and is not particularly limited as long as it satisfies the above requirements (A-1) and (A-II), and includes crystalline, low-crystalline, amorphous carbon materials and carbon materials consisting of mixtures thereof.
[0024] Among the carbon materials, examples of crystalline carbon include carbon nanotubes (e.g., single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT)), graphene (e.g., single-layered graphene, multi-layered graphene), fullerenes (e.g., Buckminsterfullerene, higher fullerenes), graphite (e.g., natural graphite, artificial graphite), diamond, etc. Examples of low-crystalline and amorphous carbon include carbon black, activated carbon, etc.
[0025] The carbon material (A) may be a carbon material that has been subjected to a surface modification or modification treatment (for example, introduction of a functional group, oxidation treatment, or reduction treatment), may contain a metal or the like, or may have some of the carbon atoms substituted with other atoms.
[0026] The carbon material (A) according to the present invention may be one produced by a conventionally known method, or a commercially available product may be used. For example, carbon nanotubes can be produced by methods such as arc discharge, laser deposition, and gas-phase chemical vapor deposition, as exemplified in JP 2009-196873 A, and surface modification treatment can be performed by methods such as those exemplified in JP 2014-501689 A. Commercially available products include "Multi Walled Carbon nanotubes NANOCYL NC7000" and "Multi Walled Carbon nanotubes NANOCYL NC3101" from Nanocyl, "Single Walled Nanotubes OH Functionalized" and "Multi Walled Nanotubes OH Functionalized" from SkySpring Nanomaterials, and "Multi-Walled Carbon Nanotubes, -OH Functionalized" from IoLiTec.
[0027] Graphene can be produced by methods such as arc discharge, laser deposition, vapor phase chemical vapor deposition, heat treatment of silicon carbide, mechanical peeling, and ultrasonic peeling after chemical oxidation, as exemplified in JP 2014-152095 A. Commercially available products include "Graphene Nanoplatelets xGnP" from XG Sciences, "Reduced Graphene Oxide", "Boron-doped Graphene Powder", "Phosphorus-doped Graphene Powder", "Sulfur-doped Graphene Powder", "Nitrogen-doped Graphene Powder", and "Graphene Film" from Graphitene.
[0028] Fullerenes are produced by methods such as arc discharge, resistance heating, laser evaporation, combustion, and pyrolysis, as exemplified in JP 2013-241379 A, and hydroxyl groups and carboxyl groups can be introduced onto the carbon of fullerenes by chemical treatment. 60 PCPA" "C 60 (OH) 22-26 " etc.
[0029] Graphite can be broadly divided into natural graphite and artificial graphite, and examples of natural graphite include flake graphite, lump graphite (flake graphite), and amorphous graphite. Artificial graphite can be produced by methods such as precipitation from Fe, Ni / C molten body, decomposition of carbides of Si, Al, etc., cooling of carbon melt under high temperature and pressure, and high-temperature decomposition and precipitation of hydrocarbon gas, as exemplified in JP-A-02-083208. Commercially available products include "High Purity Graphite Powder SP-270" and "Artificial Graphite Powder HAG-150" from Nippon Graphite Co., Ltd.
[0030] Carbon black can be produced by pyrolysis or incomplete combustion of hydrocarbons such as oil and natural gas, specifically by the furnace process, channel process, acetylene process, and pine smoke process.
[0031] Activated carbon can be produced by carbonizing and activating wood (e.g., charcoal, sawdust, bark), fruit shells (e.g., coconut shells), grain shells (e.g., rice husks), coal (e.g., grass coal, tar, coke), petroleum (e.g., tar, pitch) at high temperatures, etc. Commercially available products include "Porous Carbon CNоvel" by Toyo Tanso Co., Ltd. and "Triporous" by Sony Corporation.
[0032] The carbon material (A) is sp 2 It is preferable that the carbon nanotube has a two-dimensional sheet structure, and it is also preferable that the two-dimensional sheet has a cylindrical structure or a spherical structure. Specifically, it is preferable that the carbon nanotube has at least one selected from the group consisting of carbon nanotubes, graphene, fullerene, graphite, and activated carbon.
[0033] The carbon material (A) is not particularly limited in shape and size, and may be in the form of granules, powder, fibers, sheets, etc., but in the case of a granular or powdery shape, it is preferable that the carbon material has mesopores or macropores, since this promotes contact with the organoaluminum compound (B) and the transition metal compound (C) described below. The carbon material (A) may be dried or calcined at 50° C. or higher and 1000° C. or lower, preferably 100° C. or higher and 800° C. or lower, as required, before use.
[0034] <Organoaluminum Compounds (B)> The organoaluminum compound (B) used in the present invention is a compound represented by the following general formula (BI).
[0035] R a m Al(OR b ) n H p X q (BI) In formula (BI), R a and R brepresents a hydrocarbon group having 1 to 15 carbon atoms, which may be the same or different, X represents a halogen atom, m is an integer of 1 to 3, n is an integer of 0 to 2, p is an integer of 0 to 2, q is an integer of 0 to 2, and m+n+p+q=3.
[0036] The hydrocarbon group having 1 to 15 carbon atoms is, for example, an alkyl group, a cycloalkyl group, or an aryl group, and specific examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an isobutyl group, a pentyl group, a hexyl group, an octyl group, a cyclopentyl group, a cyclohexyl group, a phenyl group, and a tolyl group.
[0037] Specific examples of the organoaluminum compound (B) include trialkylaluminums such as trimethylaluminum, triethylaluminum, triisopropylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, and tri-2-ethylhexylaluminum; dialkylaluminum halides such as dimethylaluminum chloride, diethylaluminum chloride, diisopropylaluminum chloride, and dimethylaluminum bromide; alkylaluminum sesquihalides such as methylaluminum sesquichloride, ethylaluminum sesquichloride, isopropylaluminum sesquichloride, butylaluminum sesquichloride, and ethylaluminum sesquibromide; methylaluminum dichloride, ethylaluminum dichloride, isopropylaluminum dichloride, and ethylaluminum sesquibromide. Examples of the aluminum dihalide include alkyl aluminum dihalides such as aluminum dichloride and ethyl aluminum dibromide; alkyl aluminum hydrides such as dimethyl aluminum hydride, diethyl aluminum hydride, dihydrophenyl aluminum hydride, diisopropyl aluminum hydride, di-n-butyl aluminum hydride, diisobutyl aluminum hydride, diisohexyl aluminum hydride, diphenyl aluminum hydride, dicyclohexyl aluminum hydride, di-sec-heptyl aluminum hydride and di-sec-nonyl aluminum hydride; and dialkyl aluminum alkoxides such as dimethyl aluminum ethoxide, diethyl aluminum ethoxide, diisopropyl aluminum methoxide and diisobutyl aluminum ethoxide.
[0038] Among the above, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, diethylaluminum chloride, ethylaluminum sesquichloride, ethylaluminum dichloride, diisobutylaluminum hydride, and diethylaluminum ethoxide are particularly preferred.
[0039] <Transition metal compound (C)> The transition metal compound (C) used in the present invention is a compound represented by the following general formula (CI).
[0040] L m MX n ···(CI) In formula (CI), M is an atom selected from the group consisting of atoms of groups 3, 4, 5, 6, 7, 8, 9, 10, and 11 of the periodic table, and lanthanide atoms. It is preferably an atom of a transition metal of group 4 of the periodic table, specifically a titanium atom, a zirconium atom, or a hafnium atom.
[0041] L is a ligand, and multiple L may be the same or different from each other, and multiple L may be connected by a substituent in L, but at least one L contains at least one atom selected from the group consisting of boron, nitrogen, oxygen, phosphorus, sulfur, and selenium. Among them, it is preferable that at least one atom selected from the group consisting of boron, nitrogen, oxygen, phosphorus, sulfur, and selenium in L is covalently bonded or coordinately bonded to the M. Furthermore, it is particularly preferable that the atom bonded to the M is a nitrogen atom or an oxygen atom. m is an integer of 2 or more, and is preferably 2. n is an integer of 1 to 4 which satisfies the valence of M, and is preferably 1 or 2.
[0042] X is a leaving group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, an aluminum-containing group, a conjugated diene derivative group, and a neutral ligand capable of coordinating with a lone electron pair. When n is 2 or more, multiple Xs may be the same or different from each other, and may be bonded to each other to form a ring. Preferred are a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group, an oxygen-containing group, or a conjugated diene derivative group. The halogen atom includes fluorine, chlorine, bromine, iodine, etc., and is preferably chlorine or bromine.
[0043] Examples of the hydrocarbon group include linear or branched alkyl groups such as a methyl group, an ethyl group, a 1-propyl group, a 1-butyl group, a 1-pentyl group, a 1-hexyl group, a 1-heptyl group, a 1-octyl group, an isopropyl group, a sec-butyl group (butan-2-yl group), a tert-butyl group (2-methylpropan-2-yl group), an isobutyl group (2-methylpropyl group), a pentan-2-yl group, a 2-methylbutyl group, an isopentyl group (3-methylbutyl group), a neopentyl group (2,2-dimethylpropyl group), a cyamyl group (1,2-dimethylpropyl group), an isohexyl group (4-methylpentyl group), a 2,2-dimethylbutyl group, a 2,3-dimethylbutyl group, a 3,3-dimethylbutyl group, a thexyl group (2,3-dimethylbut-2-yl group), and a 4,4-dimethylpentyl group; Vinyl group, allyl group, propenyl group (prop-1-en-1-yl group), iso-propenyl group (prop-1-en-2-yl group), allenyl group (prop-1,2-dien-1-yl group), but-3-en-1-yl group, crotyl group (but-2-en-1-yl group), but-3-en-2-yl group, methallyl group (2-methylallyl group), buta-1,3-dienyl group, pentaerythritol group, linear or branched alkenyl groups or unsaturated double bond-containing groups, such as ter-4-en-1-yl group, pent-3-en-1-yl group, pent-2-en-1-yl group, iso-pentenyl group (3-methylbut-3-en-1-yl group), 2-methylbut-3-en-1-yl group, pent-4-en-2-yl group, and prenyl group (3-methylbut-2-en-1-yl group); linear or branched alkynyl groups or unsaturated triple bond-containing groups, such as ethynyl, prop-2-yn-1-yl, and propargyl (prop-1-yn-1-yl); aromatic linear or branched alkyl groups and unsaturated double bond-containing groups, such as benzyl, 2-methylbenzyl, 4-methylbenzyl, 2,4,6-trimethylbenzyl, 3,5-dimethylbenzyl, cuminyl (4-isopropylbenzyl), 2,4,6-tri-isopropylbenzyl, 4-tert-butylbenzyl, 3,5-di-tert-butylbenzyl, 1-phenylethyl, benzhydryl (diphenylmethyl), and cumyl; cyclic saturated hydrocarbon groups such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cycloheptatrienyl group, a norbornyl group, a norbornenyl group, a 1-adamantyl group, and a 2-adamantyl group; Aromatic substituents (aryl groups) such as phenyl, tolyl (methylphenyl), xylyl (dimethylphenyl), mesityl (2,4,6-trimethylphenyl), cumenyl (isopropylphenyl), julyl (2,3,5,6-tetramethylphenyl), 2,6-diisopropylphenyl, 2,4,6-triisopropylphenyl, 4-tert-butylphenyl, 3,5-ditert-butylphenyl, naphthyl, biphenyl, terphenyl, binaphthyl, acenaphthalenyl, phenanthryl, anthracenyl, pyrenyl, and ferrocenyl. Among the above hydrocarbon groups, a methyl group, an iso-butyl group, a neopentyl group, a cyamyl group, a benzyl group, a phenyl group, a tolyl group, a xylyl group, a mesityl group, and a cumenyl group are preferable.
[0044] Examples of the halogen-containing group include a fluoromethyl group, a trifluoromethyl group, a trichloromethyl group, a pentafluoroethyl group, a 2,2,2-trifluoroethyl group, a fluorophenyl group, a difluorophenyl group, a trifluorophenyl group, a tetrafluorophenyl group, a pentafluorophenyl group, a trifluoromethylphenyl group, a bistrifluoromethylphenyl group, and a hexachloroantimonate anion. Among the halogen-containing groups, a pentafluorophenyl group is preferable.
[0045] Examples of the silicon-containing group include a trimethylsilyl group, a triethylsilyl group, a tri-isopropylsilyl group, a diphenylmethylsilyl group, a tert-butyldimethylsilyl group, a tert-butyldiphenylsilyl group, a triphenylsilyl group, a tris(trimethylsilyl)silyl group, a trimethylsilylmethyl group, etc. Among the silicon-containing groups, a trimethylsilylmethyl group is preferred.
[0046] Examples of the oxygen-containing group include alkoxy groups such as a hydroxyl group, a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an allyloxy group, an n-butoxy group, a sec-butoxy group, an isobutoxy group, a tert-butoxy group, a benzyloxy group, and a methoxymethoxy group; aryloxy groups such as a phenoxy group, a 2,6-dimethylphenoxy group, a 2,6-di-isopropylphenoxy group, a 2,6-di-tert-butylphenoxy group, a 2,4,6-trimethylphenoxy group, and a 2,4,6-tri-isopropylphenoxy group; a furyl group, a benzofuryl group, a tetrahydrofuryl group, a pyranyl group, a tetrahydropyranyl group, an acetoxy group, a pivaloyloxy group, a benzoyloxy group, a trifluoroacetoxy group, a perchlorate anion, and a periodate anion. Among the oxygen-containing groups, a methoxy group, an ethoxy group, an iso-propoxy group, and a tert-butoxy group are preferred.
[0047] Examples of the sulfur-containing group include mesyl group (methanesulfonyl group), phenylsulfonyl group, tosyl group (p-toluenesulfonyl group), triflyl group (trifluoromethanesulfonyl group), nonaflyl group (nonafluorobutanesulfonyl group), thiophenyl group, mesylate group (methanesulfonate group), tosylate group (p-toluenesulfonate group), triflate group (trifluoromethanesulfonate group), nonaflate group (nonafluorobutanesulfonate group), thiophene group, benzothiophene group, etc. Among the sulfur-containing groups, triflate (trifluoromethanesulfonate) is preferred.
[0048] Examples of the nitrogen-containing group include an amino group, a cyano group, a methylamino group, a dimethylamino group, an ethylamino group, a diethylamino group, an allylamino group, a diallylamino group, a benzylamino group, a dibenzylamino group, a nitro group, a pyrrolidinyl group, a piperidinyl group, a morpholyl group, a pyrrolyl group, a bistriflyl imide group, a pyridinyl group, a pyrimidinyl group, a quinolinyl group, a triazinyl group, an oxazoline group, an imidazole group, an indole group, a carbazole group, etc. Among the nitrogen-containing groups, a dimethylamino group, a diethylamino group, a pyrrolidinyl group, a pyrrolyl group, and a bistriflyl imide group are preferred.
[0049] The phosphorus-containing group may, for example, be a hexafluorophosphate anion. Examples of the boron-containing group include tetrafluoroborate anion, tetrakis(pentafluorophenyl)borate anion, (methyl)(tris(pentafluorophenyl))borate anion, (benzyl)(tris(pentafluorophenyl))borate anion, tetrakis((3,5-bistrifluoromethyl)phenyl)borate anion, and groups represented by BR4 (each R independently represents hydrogen, an alkyl group, an aryl group which may have a substituent, a halogen atom, or the like).
[0050] Examples of the aluminum-containing group include [ka] or [ka] A four-membered ring represented by (M represents M in the general formula [3] or [4].) Examples of the group include a group represented by AlR4 (R represents hydrogen, an alkyl group, an aryl group which may have a substituent, a halogen atom, or the like) which can form the following formula:
[0051] Examples of the conjugated diene derivative group include a 1,3-butadienyl group, an isoprenyl group (2-methyl-1,3-butadienyl group), a piperylenyl group (1,3-pentadienyl group), a 2,4-hexadienyl group, a 1,4-diphenyl-1,3-pentadienyl group, a cyclopentadienyl group, and a metallocyclopentene group.
[0052] Examples of neutral ligands capable of coordinating with lone electron pairs include ethers such as diethyl ether, tetrahydrofuran, dioxane, and 1,2-dimethoxyethane; amines such as triethylamine and diethylamine; heterocyclic compounds such as pyridine, picoline, lutidine, oxazoline, oxazole, thiazole, imidazole, and thiophene; and organic phosphorus compounds such as triphenylphosphine, tricyclohexylphosphine, and tri-tert-butylphosphine.
[0053] The hydrocarbon group, the halogen-containing group, the silicon-containing group, the oxygen-containing group, the sulfur-containing group, the nitrogen-containing group, the phosphorus-containing group, the boron-containing group, the aluminum-containing group, the conjugated diene-based divalent derivative group, and the neutral ligand capable of coordinating with a lone electron pair may be further substituted with another substituent.
[0054] Examples of such transition metal compounds (C) include those described in JP 2003-206310 A, JP 2020-117711 A, JP 2009-537656 A, JP 2017-520548 A, JP 2004-269825 A, JP 2011-127121 A, JP 2016-527182 A, and JP 2017-535518 A, and preferably at least one compound selected from the group consisting of transition metal compounds represented by the following general formulas (C-II), (C-III), (C-IV), (CV), and (C-VI).
[0055] [ka]
[0056] In the general formula (C-II), M represents a transition metal atom of Group 4 or Group 5 of the periodic table, specifically a titanium atom, a zirconium atom, a hafnium atom, a vanadium atom, a niobium atom, or a tantalum atom. It is preferably a transition metal atom of Group 4 of the periodic table, specifically a titanium atom, a zirconium atom, or a hafnium atom, and particularly preferably a titanium atom or a zirconium atom.
[0057] In the general formula (C-II), the dotted line connecting the nitrogen atom (N) and M generally indicates that the nitrogen atom (N) is coordinated to M, but in the present invention, it may or may not be coordinated.
[0058] R 1 , R 2 , R 3 , R 4 and R 5 may be the same or different and represent a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, a germanium-containing group, or a tin-containing group, and two or more of these may be linked to each other to form a ring.
[0059] Specific examples of the halogen atom, hydrocarbon group, halogen-containing group, silicon-containing group, oxygen-containing group, sulfur-containing group, nitrogen-containing group, phosphorus-containing group, and boron-containing group include the same as those exemplified as X in the general formula (CI), and the germanium-containing group or tin-containing group includes groups in which the silicon of the silicon-containing group is substituted with germanium or tin. In addition, structures having the halogen-containing group, silicon-containing group, oxygen-containing group, sulfur-containing group, nitrogen-containing group, phosphorus-containing group, and boron-containing group as substituents in the hydrocarbon group are also included in R. 1 , R 2 , R 3 , R 4 , R 5 The following can be given as an example.
[0060] Examples of the hydrocarbon group include linear or branched alkyl groups having 1 to 30 carbon atoms, preferably 1 to 20 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a neopentyl group, and an n-hexyl group; aryl groups having 6 to 30 carbon atoms, preferably 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, a biphenyl group, a terphenyl group, a phenanthryl group, or an anthracenyl group; These aryl groups are preferably substituted with 1 to 5 substituents such as a halogen atom, an alkyl group or alkoxy group having 1 to 30 carbon atoms, preferably 1 to 20 carbon atoms, or an aryl group or aryloxy group having 6 to 30 carbon atoms, preferably 6 to 20 carbon atoms.
[0061] R 1 is preferably a group selected from a linear or branched hydrocarbon group having 1 to 20 carbon atoms, an alkyl group having 3 to 20 carbon atoms, and an aryl group having 6 to 20 carbon atoms, from the viewpoint of olefin polymerization catalyst activity and of providing a high-molecular-weight ethylene polymer.
[0062] R 6is selected from a hydrogen atom, a hydrocarbon group having 1 to 3 carbon atoms consisting only of primary or secondary carbon, an alkyl group having 4 or more carbon atoms, an aryl-substituted alkyl group, a monocyclic or bicyclic cyclic hydrocarbon group, an aryl group, and a halogen atom. Among these, from the viewpoint of olefin polymerization catalyst activity and from the viewpoint of providing a high molecular weight ethylene polymer, it is preferably a group selected from an alkyl group having 4 or more carbon atoms, an aryl-substituted alkyl group, a monocyclic or bicyclic cyclic hydrocarbon group, and an aryl group, and more preferably includes a branched alkyl group such as a tert-butyl group; an aryl-substituted alkyl group such as a benzyl group, a 1-methyl-1-phenylethyl group (cumyl group), a 1-methyl-1,1-diphenylethyl group, or a 1,1,1-triphenylmethyl group (trityl group); or a cyclic hydrocarbon group having a ring structure having 6 to 15 carbon atoms, such as a cyclohexyl group, an adamantyl group, a norbornyl group, or a tetracyclododecyl group.
[0063] X is a leaving group, and is a substituent selected from the group consisting of hydrogen atoms, halogen atoms, hydrocarbon groups, anionic ligands, and neutral ligands capable of coordinating with lone electron pairs, and the anionic ligand is a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, an aluminum-containing group, or a conjugated diene derivative group. When n is 2 or more, the multiple Xs may be the same or different from each other, and may be bonded to each other to form a ring. Preferred are hydrogen atoms, halogen atoms, hydrocarbon groups having 1 to 20 carbon atoms, silicon-containing groups, oxygen-containing groups, or conjugated diene derivative groups. Specific examples of X include the same as those exemplified as X in the above general formula (CI). n is an integer of 1 to 4 satisfying the valence of M, and is preferably 1 or 2.
[0064] [ka]
[0065] In the general formulae (C-III) and (C-IV), M represents a transition metal atom of Group 4 of the periodic table, specifically a titanium atom, a zirconium atom, or a hafnium atom, and preferably a titanium atom.
[0066] R 7 may be the same or different, and each represents a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, a germanium-containing group, or a tin-containing group; adjacent R 7 may be bonded to each other to form a monocyclic or bicyclic ring which may have a substituent. Specific examples of the halogen atom, the hydrocarbon group, the halogen-containing group, the silicon-containing group, the oxygen-containing group, the sulfur-containing group, the nitrogen-containing group, the phosphorus-containing group, the boron-containing group, the germanium-containing group, and the tin-containing group include R 1 , R 2 , R 3 , R 4 , R 5 Examples of the above-mentioned examples include those similar to those given as examples.
[0067] R 7 R is preferably a hydrocarbon group having 1 to 25 carbon atoms, an oxygen-containing group having 1 to 25 carbon atoms, or a nitrogen-containing group having 1 to 25 carbon atoms. 7 When the ring forms a monocyclic or bicyclic ring which may have a substituent, it is preferable to form the ring as a 4- to 8-membered saturated or unsaturated heterocycle which may have a substituent containing a phosphorus atom or a boron atom.
[0068] Cp is a cyclopentadienyl ligand which may have a substituent. Among the substituents, adjacent substituents may be bonded to each other to form a ring which may have a substituent.
[0069] The cyclopentadienyl-type ligand is a substituted ligand having a five-membered carbon ring bonded to a metal by a π-type bond, and includes substituted cyclopentadienyl-type ligands such as substituted cyclopentadienyl ligands, substituted tetrahydroindenyl ligands, substituted octahydrofluorenyl ligands, substituted hydroazulenyl ligands, substituted pentahydroazulenyl ligands, substituted dihydrocyclopentenoannulene ligands, substituted cyclopentenopyrrole ligands, substituted cyclopentenothiophene ligands, and substituted cyclopentenodithiophene ligands, substituted indenyl-type ligands such as substituted indenyl ligands, substituted tetrahydroindenyl ligands, substituted benzoindenyl ligands, substituted dihydroindacenyl ligands, substituted indenopyrrole ligands, substituted indenoindole ligands, and substituted indenothiophenes, and substituted fluorenyl ligands. As the cyclopentadienyl type ligand, a substituted cyclopentadienyl type ligand and a substituted indenyl type ligand are preferred, and a substituted cyclopentadienyl ligand, a substituted dihydrocyclopentenoannulene ligand, a substituted cyclopentenothiophene ligand, a substituted cyclopentenodithiophene ligand, and a substituted indenyl ligand are more preferred.
[0070] The substituents of the cyclopentadienyl ligand are each independently a hydrogen atom, a hydrocarbon group having 1 to 40 carbon atoms, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a nitrogen-containing group, or a sulfur-containing group.
[0071] Specific examples of the hydrocarbon group, halogen-containing group, silicon-containing group, oxygen-containing group, nitrogen-containing group and sulfur-containing group in the substituent of the cyclopentadienyl ligand include the above-mentioned R 7 Examples of the hydrocarbon group, halogen-containing group, silicon-containing group, oxygen-containing group, nitrogen-containing group and sulfur-containing group in the above formula include the same groups as those exemplified above.
[0072] Z is an atom of Group 15 or 16 of the periodic table, and is preferably a nitrogen atom or an oxygen atom. Y is a phosphorus atom or a boron atom. The solid lines are covalent or coordinate bonds, and the dotted lines are covalent bonds that exist when Z is a Group 15 element.
[0073] y is 2 when Z is an atom of a Group 15 element, and y is 3 when Z is an atom of a Group 16 element. z is 3 when Z is an atom of a Group 15 element, and is 4 when Z is an atom of a Group 16 element.
[0074] X is a leaving group, and is a substituent selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, an anionic ligand, and a neutral ligand capable of coordinating with a lone electron pair, and the anionic ligand is a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, an aluminum-containing group, or a conjugated diene derivative group. When n is 2 or more, the multiple Xs may be the same or different from each other, and may be bonded to each other to form a ring. It is preferably a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group, an oxygen-containing group, or a conjugated diene derivative group.
[0075] Specific examples of X include the same as those exemplified as X in the above general formula (CI), and n is an integer of 1 to 4 satisfying the valence of M, and is preferably 1 or 2. n is an integer of 1 to 4 satisfying the valence of M, and is preferably 1 or 2.
[0076] [ka]
[0077] In the general formulae (CV) and (C-VI), M represents an atom selected from the group consisting of atoms of Groups 3, 4, 5, and 6 of the periodic table, or lanthanide atoms, and is preferably a transition metal atom of Group 4 of the periodic table, specifically, a titanium atom, a zirconium atom, or a hafnium atom.
[0078] In the above general formulae (CV) and (C-VI), Z α and Zβ Of the four dotted lines connecting M and M, at least two are covalent bonds, and the remaining bonds are coordinate bonds. However, in the present invention, the bonds showing coordinate bonds may or may not be coordinated.
[0079] Z α When M forms a covalent bond with Z α may be the same or different and are selected from a nitrogen atom or a phosphorus atom; Z α does not form a covalent bond with M, Z α may be the same or different, and each represents an oxygen atom, a sulfur atom, -NR α - and -PR α - is selected from the group consisting of:
[0080] Z β When M forms a covalent bond with Z β may be the same or different, and each represents an oxygen atom, a sulfur atom, -NR β - and -PR β -, wherein Z β does not form a covalent bond with M, Z β may be the same or different, -OR β , -SR β , -NR β 2, and -PR β 2.
[0081] R α , R β may be the same or different, and each represents a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, or a boron-containing group. Specific examples thereof include R 1 , R 2 , R 3 , R 4 , R 5 Examples of the above-mentioned examples include those similar to those given as examples.
[0082] R 8is a bridging group containing 1 to 50 atoms (hydrogen atoms are not included in the number), and preferred structures include linear or branched alkyl groups, alkyl groups containing cyclic saturated hydrocarbons, and alkyl groups containing aromatic hydrocarbons. Among these, linear or branched alkyl groups and alkyl groups containing cyclic saturated hydrocarbons are particularly preferred, and specific examples include a methylene group, an ethylene group, a trimethylene group, a pentane-2,4-diyl group, and a cyclohexane-1,2-dimethylene group.
[0083] R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 , R 22 , R 23 and R 24 may be the same or different, and each represents a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, or a boron-containing group. Specific examples thereof include R 1 , R 2 , R 3 , R 4 , R 5 Two or more of these may be linked together to form a ring. 10 , R 18 At least one of them is not hydrogen, and R 10 , R 18 It is particularly preferred that both are selected from the group consisting of an optionally substituted aryl group, or an optionally substituted aryl group containing one or more heteroatoms in the aromatic ring of the aryl group.
[0084] X is a leaving group, and is a substituent selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, an anionic ligand, and a neutral ligand capable of coordinating with a lone electron pair, and the anionic ligand is a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, an aluminum-containing group, or a conjugated diene derivative group. When n is 2 or more, the multiple Xs may be the same or different from each other, and may be bonded to each other to form a ring. It is preferably a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group, an oxygen-containing group, or a conjugated diene derivative group.
[0085] Specific examples of X include the same as those exemplified as X in the above general formula (CI), and n is an integer of 1 to 4 satisfying the valence of M, and is preferably 1 or 2. n is an integer of 1 to 4 satisfying the valence of M, and is preferably 1 or 2.
[0086] A carbon material (A) that satisfies the requirements (AI) and (A-II); An organoaluminum compound (B) represented by the general formula (BI), A transition metal compound (C) represented by the general formula (CI), The olefin polymerization catalyst of the present invention, which comprises the above compound, can produce an olefin polymer having a carbon material efficiently dispersed therein with high polymerization activity.
[0087] The reason why the present invention exhibits its effects is not entirely clear, but the inventors speculate as follows. By contacting the oxygen atoms in the carbon material (A) with the organoaluminum compound (B), a chemical species generally called a cocatalyst is formed, which exhibits the catalytic activity of the transition metal compound (C). After contacting this chemical species with the transition metal compound (C), an olefin polymer can be produced by polymerizing the olefin. In this case, by using a carbon material (A) that satisfies the above requirements (AI) and (A-II), it is possible to form more of the chemical species that can come into contact with the transition metal compound (C), and by using the transition metal compound (C) represented by the above general formula (CI), it is possible to form more of the sp 2 It is presumed that the unique electronic properties of the two-dimensional sheet structure formed by bonded carbon result in electronic interaction with the heteroatoms in the transition metal compound (C) represented by the general formula (CI) above, resulting in an olefin polymerization catalyst that exhibits significantly higher olefin polymerization activity.
[0088] This is a surprising result considering that in Comparative Example 1 of JP 2003-206310 A, no catalytic activity was exhibited when a contact product of an oxygen atom-containing compound (alcohol) and an organoaluminum compound was used for a transition metal compound having a heteroatom, and it can be said that this is a technology that even a person skilled in the art would not easily discover.
[0089] <Method for preparing olefin polymerization catalyst> One of the preferred embodiments of the olefin polymerization catalyst of the present invention is a solid catalyst component (X) prepared by contacting the carbon material (A), the organoaluminum compound (B) and the transition metal compound (C).
[0090] It is preferable that the organoaluminum compound (B) and the transition metal compound (C) are diluted with an inert solvent if they are liquid, or dissolved in an inert solvent if they are solid, and then contacted with the carbon material (A). Examples of inert solvents that can be used include aromatic hydrocarbons such as benzene, toluene, and xylene, aliphatic saturated hydrocarbons such as hexane, heptane, and decane, alicyclic hydrocarbons such as cyclohexane and methylcyclopentane, halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane, and mixtures thereof.
[0091] The method for contacting the carbon material (A), the organoaluminum compound (B), and the transition metal compound (C) is not particularly limited as long as the effects of the present invention are achieved. For example, a method of adding an inert solvent containing the organoaluminum compound (B) or the transition metal compound (C) to the carbon material (A) and impregnating it into the pores of the carbon material (A), a method of immersing the carbon material (A) in an inert solvent containing the organoaluminum compound (B) or the transition metal compound (C) and leaving it to stand, a method of mixing the carbon material (A) with an inert solvent containing the organoaluminum compound (B) or the transition metal compound (C) by stirring or the like, a method of passing an inert solvent containing the organoaluminum compound (B) or the transition metal compound (C) through the carbon material (A), and the like may be used. The carbon material (A) may be physically or chemically fixed on a solid support (including powder, granulated particles, fibers, films, and the like), and a heating operation may be performed during the contact.
[0092] Among these, a method in which the carbon material (A) is mixed with an inert solvent containing the organoaluminum compound (B) or the transition metal compound (C) by stirring or the like is preferred. After the contact operation, if necessary, the contact liquid is left to stand and the supernatant is removed, or the inert solvent is removed by a method such as filtration, and if necessary, the mixture is washed with the inert solvent.
[0093] The temperature when the heating operation is performed varies depending on the solvent used, but is usually from the freezing point of the solvent to 200° C. or less, preferably 150° C. or less. The contact time varies depending on the contact method and temperature, but is usually from 30 seconds to 1,000 hours, preferably from 5 minutes to 120 hours. In any step of the contact method, by adding component (G), fouling during the polymerization reaction can be suppressed to a higher degree and the particle properties of the resulting polymer can be further improved. As component (G), a compound having a polar functional group can be used, and a nonionic surfactant is preferable, and a polyalkylene oxide block, a higher aliphatic amide, a polyalkylene oxide, a polyalkylene oxide alkyl ether, an alkyldiethanolamine, a polyoxyalkylene alkylamine, a glycerin fatty acid ester, or an N-acyl amino acid is more preferable. These may be used alone or in combination of two or more kinds.
[0094] The order of contacting the carbon material (A), the organoaluminum compound (B) and the transition metal compound (C) is not particularly limited as long as the effects of the present invention can be obtained. A step (1-1) of contacting the carbon material (A) with the organoaluminum compound (B); a step (1-2) of contacting the contact product obtained in the step (1-1) with the transition metal compound (C) to obtain a solid catalyst component (X); A step (2-1) of contacting the carbon material (A) with the organoaluminum compound (B); A step (2-2) of contacting the transition metal compound (C) with the organoaluminum compound (B); and a step (2-3) of contacting the contact product obtained in the step (2-1) with the contact product obtained in the step (2-2) to obtain a solid catalyst component (X). In this case, the organoaluminum compound (B) used in the step (2-1) and the step (2-2) may be the same or different.
[0095] In the steps (1-1) and (2-1), the organoaluminum compound (B) can be used in an amount of preferably 0.1 mmol or more and 500 mmol or less, more preferably 0.2 mmol or more and 200 mmol or less, and even more preferably 0.5 mmol or more and 100 mmol or less, per 1 g of the carbon material (A).
[0096] In the step (2-2), the organoaluminum compound (B) can be used in an amount of preferably 0.1 mmol or more and 3000 mmol or less, more preferably 0.5 mmol or more and 1000 mmol or less, and even more preferably 1 mmol or more and 500 mmol or less, per 1 mmol of the transition metal compound (C).
[0097] In the steps (1-2) and (2-3), the transition metal compound (C) can be used in an amount of preferably 0.1 μmol to 1000 μmol, more preferably 0.5 μmol to 500 μmol, and even more preferably 1 μmol to 200 μmol, per 1 g of the carbon material (A).
[0098] In the production of olefin polymers, the solid catalyst component (X) may be used in a state of being suspended in an inert hydrocarbon or in a dried state, or may be used after being prepolymerized with an olefin which may be the same as or different from the olefin used in the production of the olefin polymer.
[0099] [Production method of olefin polymer] The process for producing an olefin polymer of the present invention is characterized by comprising a step of polymerizing an olefin in the presence of the above-mentioned olefin polymerization catalyst of the present invention. In the present invention, the term "polymerization" may include copolymerization such as random copolymerization and block copolymerization in addition to homopolymerization.
[0100] The olefins to be polymerized in the present invention include ethylene, α-olefins, and cyclic olefins. Among these, the α-olefin may be a linear or branched α-olefin having 3 to 30 carbon atoms, preferably 3 to 20 carbon atoms. More specifically, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene are preferred. Among these, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 3-methyl-1-pentene are preferred, and propylene, 1-butene, 1-hexene, and 4-methyl-1-pentene are more preferred.
[0101] Examples of the cyclic olefin include cyclic olefins having 3 to 30 carbon atoms, and preferably having 3 to 20 carbon atoms. More specific examples include cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and 2-methyl-1,4,5,8-dimethano-1,2,3,4,4a,5,8,8a-octahydronaphthalene.
[0102] The step of polymerizing an olefin is preferably a step of homopolymerizing ethylene or a step of copolymerizing ethylene and an α-olefin having 3 to 20 carbon atoms in the presence of the solid catalyst component (X).
[0103] In the method for producing an olefin polymer of the present invention, the polymerization can be carried out by either a liquid phase polymerization method such as suspension polymerization or a gas phase polymerization method. Examples of the inert hydrocarbon medium used in the liquid phase polymerization method include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane, and mixtures thereof, and the olefin itself can also be used as the solvent.
[0104] In the method of the present invention, the lower limit of the temperature for polymerizing the olefin is -20°C, preferably 0°C, more preferably 20°C, and particularly preferably 30°C, and the upper limit of the temperature for polymerizing the olefin is 200°C, preferably 150°C, more preferably 100°C, and particularly preferably 80°C.
[0105] The polymerization pressure in the method of the present invention is usually from atmospheric pressure to 10 MPa, preferably from atmospheric pressure to 5 MPa, and the polymerization reaction can be carried out in any of a batch system, a semi-continuous system, and a continuous system. The process for producing an olefin polymer of the present invention may be a so-called multi-stage polymerization process in which the polymerization reaction is carried out in two or more stages under different polymerization reaction conditions.
[0106] The molecular weight of the resulting olefin polymer can be adjusted by making hydrogen present in the polymerization system or by changing the polymerization temperature. In the step of polymerizing the olefin, the component (G) can be present in order to suppress adhesion (fouling) to a polymerization reactor or to improve particle properties.
[0107] <Olefin polymer> One embodiment of the olefin polymer obtained by the method for producing an olefin polymer of the present invention is an ethylene-based polymer containing ethylene-derived structural units in a range of preferably 90 mol% to 100 mol%, more preferably 95 mol% to 100 mol%. The ethylene-based polymer contains α-olefin-derived structural units having 3 to 20 carbon atoms in a total amount of preferably 0 mol% to 10 mol%, more preferably 0 mol% to 5 mol%, where the sum of the content of ethylene-derived structural units and the content of α-olefin-derived structural units having 3 to 20 carbon atoms is taken as 100 mol%.
[0108] Among these polymers, ethylene homopolymer, ethylene / propylene copolymer, ethylene / 1-butene copolymer, ethylene / propylene / 1-butene copolymer, ethylene / 1-octene polymer, ethylene / 1-hexene polymer, ethylene / 4-methyl-1-pentene polymer, ethylene / propylene / 1-octene polymer, ethylene / propylene / 1-hexene polymer, and ethylene / propylene / 4-methyl-1-pentene polymer are preferred. Also, so-called block copolymers (impact copolymers) obtained by mixing or continuously producing two or more types selected from these polymers may be used.
[0109] The olefin polymer obtained by the method for producing an olefin polymer contains the carbon material (A) in an amount of preferably 0.01% by weight to 25% by weight, more preferably 0.02% by weight to 10% by weight. The carbon material (A) is efficiently dispersed in the olefin polymer, and is expected to have high thermal conductivity, electrical conductivity, and weather resistance. EXAMPLES
[0110] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0111] [Carbon materials] The following carbon materials (A-1) to (A-8) and (A'-9) to (A'-11) were used as the carbon materials. Each of the carbon materials was dried under reduced pressure at 100°C for 3 hours before use, and then cooled to room temperature under a nitrogen atmosphere before being used in the preparation of the solid catalyst component (X).
[0112] Carbon material (A-1): XG Sciences Graphene Nanoplatelets xGnP C750 Carbon material (A-2): XG Sciences Graphene Nanoplatelets xGnP C500 Carbon material (A-3): XG Sciences Graphene Nanoplatelets xGnP C300 Carbon material (A-4): XG Sciences Graphene Nanoplatelets xGnP M25 Carbon material (A-5): Graphitene Reduced Graphene Oxide Carbon material (A-6): Nippon Graphite Co., Ltd. High purity graphite powder SP-270 Carbon material (A-7): Nanocyl Multi Walled Carbon nanotubes NANOCYL NC3101 Carbon materials (A-8): Toyo Tanso Co., Ltd. Porous carbon CNоvel MJ(4)010) Carbon materials (A'-9): Graphitene Graphene Nanocarbon platelets - Powder Carbon material (A'-10): Nippon Graphite Co., Ltd., exfoliated graphite powder UP-5N Carbon material (A'-11): Southwest Nanotechnologies Single Walled Carbon nanotubes Signis SG65i
[0113] Oxygen content The oxygen content of the carbon material was determined by X-ray photoelectron spectroscopy (XPS) ("AXIS-NOVA" manufactured by KRATOS). The sample was dried under reduced pressure at 100°C for 3 hours, then handled under a nitrogen atmosphere and measured using a monochromated AlKα X-ray source. Charge correction and neutralization were performed during the measurement. The oxygen atom concentration was determined from the peak area of the O1s narrow spectrum, and the carbon atom concentration was determined from the peak area of the C1s narrow spectrum, and the molar ratio of oxygen atoms / carbon atoms was calculated. The results are shown in Table 1.
[0114] ≪Specific surface area≫ The specific surface area of the carbon material was measured by measuring the adsorption / desorption isotherm using nitrogen gas adsorption (Microtrack-Bell's "BELSORP-max") at liquid nitrogen temperature. The specific surface area was determined using the BET multipoint method as an analytical method. The analysis results are shown in Table 1.
[0115] [Organoaluminum compounds] The organoaluminum compounds used were the following organoaluminum compounds (B-1) to (B-3). The organoaluminum compounds (B-1) to (B-3) were used after being diluted to 1.0 mol / L in decane solution.
[0116] ·Organoaluminum compound (B-1): Tosoh Finechem Corporation, triisobutylaluminum (TIBAL) ·Organoaluminum compound (B-2): Tosoh Finechem Corporation Triethylaluminum (TEAL) ·Organoaluminum compound (B-3): Tosoh Finechem Co., Ltd. Diethylaluminum ethoxide (DEAL-E)
[0117] [Transition metal compounds] As the transition metal compounds, transition metal compounds (C-1) to (C-5) and (C'-6) to (C'-7) represented by the following formulas (C-1) to (C-5) and (C'-6) to (C'-7) were produced by known methods and used. [ka]
[0118] <Identification of transition metal compounds> The structure of the transition metal compound is 270MHz 1 The determination was made by measurement using a H-NMR (GSH-270 manufactured by JEOL Ltd.) according to a conventional method.
[0119] [Preparation of solid catalyst component (X)] <Preparation Example 1> In a Schlenk flask with a volume of 30 mL and thoroughly purged with nitrogen, 100 mg of carbon material (A-1) and 5 mL of toluene were added, and stirring was started using a rotor. 0.25 mL of a decane solution of organoaluminum compound (B-1) (0.25 mmol in terms of organoaluminum compound (B-1)) was added to this suspension, and stirring was continued at room temperature for 30 minutes. After that, 3.0 μmol of transition metal compound (C-1) was added as a toluene solution, and stirring was continued for another 30 minutes at room temperature to prepare a slurry of solid catalyst component (X-1) with a solid concentration of carbon material (A-1) of 10.0 g / L.
[0120] <Preparation Examples 2 to 11> Slurries of solid catalyst components (X-2) to (X-11) were prepared in the same manner as in Preparation Example 1, except that carbon materials (A-2) to (A-8) and (A'-9) to (A'-11) were used instead of the carbon material (A-1).
[0121] <Preparation Example 12> A slurry of a solid catalyst component (X-12) was prepared in the same manner as in Preparation Example 1, except that the amount of the organoaluminum compound (B-1) added was changed to 0.10 mmol calculated as the organoaluminum compound (B-1).
[0122] <Preparation Examples 13 and 14> Slurries of solid catalyst components (X-13) and (X-14) were prepared in the same manner as in Preparation Example 1, except that organoaluminum compounds (B-2) and (B-3) were used instead of the organoaluminum compound (B-1).
[0123] <Preparation Example 15> A slurry of a solid catalyst component (X-15) was prepared in the same manner as in Preparation Example 1, except that the organoaluminum compound (B-1) was not used.
[0124] <Preparation Examples 16-21> Slurries of solid catalyst components (X-16) to (X-21) were prepared in the same manner as in Preparation Example 1, except that the transition metal compounds (C-2) to (C-5) and (C'-6) to (C'-7) were used instead of the transition metal compound (C-1).
[0125] [Production of olefin polymers] <Example 1> In a nitrogen atmosphere, 500 milliliters of heptane was added to a SUS autoclave reactor with a capacity of 1 liter, which had been thoroughly substituted with nitrogen, and ethylene was then passed through to saturate the reactor with ethylene. Next, 0.375 mL of a decane solution of the organoaluminum compound (B-1) (0.375 mmol in terms of organoaluminum compound (B-1)) and a slurry equivalent to 30 mg of the solid content of the carbon material (A-1) were extracted from the slurry of the solid catalyst component (X-1) obtained in Preparation Example 1 and charged into the reactor. Then, the temperature and pressure were raised to 80°C and 0.8 MPaG with ethylene, and a polymerization reaction was carried out for 60 minutes at a rotation speed of 350 rpm. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80°C for 10 hours, yielding 53.8 g of an olefin polymer.
[0126] <Examples 2 to 8 and Comparative Examples 1 to 3> Polymerization reaction was carried out in the same manner as in Example 1, except that the solid catalyst component (X-1) was replaced with the slurries of the solid catalyst components (X-2) to (X-8) obtained in Preparation Examples 2 to 8, and the amounts of the solid carbon material listed in Table 1 were charged into the reactor. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80° C. for 10 hours, to obtain the amount of olefin polymer shown in Table 1.
[0127] <Comparative Examples 1 to 3> Polymerization reaction was carried out in the same manner as in Example 1, except that the solid catalyst component (X-1) was replaced with the slurries of the solid catalyst components (X-9) to (X-11) obtained in Preparation Examples 9 to 11, and the amounts of the solid carbon material listed in Table 1 were charged into the reactor. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80°C for 10 hours, to obtain the amount of olefin polymer shown in Table 1.
[0128] [Table 1]
[0129] It can be seen that the carbon material (A) constituting the olefin polymerization catalyst of the embodiment has both a high specific surface area and oxygen content, and thus a larger amount of olefin polymer can be obtained compared to the comparative example in which a carbon material having a low specific surface area or oxygen content was used.
[0130] <Example 9> A polymerization reaction was carried out in the same manner as in Example 1, except that the slurry of the solid catalyst component (X-12) obtained in Preparation Example 12 was used instead of the solid catalyst component (X-1), and the amount of the carbon material (A) solid content shown in Table 2 was charged into the reactor. After the reaction was completed, the content in the reactor was filtered and dried under reduced pressure at 80°C for 10 hours, thereby obtaining the amount of olefin polymer shown in Table 2.
[0131] <Examples 10 to 11> Polymerization reaction was carried out in the same manner as in Example 1, except that organoaluminum compounds (B-2) to (B-3) were used instead of organoaluminum compound (B-1), slurries of solid catalyst components (X-13) to (X-14) obtained in Preparation Examples 13 to 14 were used instead of solid catalyst component (X-1), and the amount of carbon material (A) solid matter listed in Table 2 was charged into the reactor. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80° C. for 10 hours, to obtain the amount of olefin polymer shown in Table 2.
[0132] <Comparative Example 4> A polymerization reaction was carried out in the same manner as in Example 1, except that no organoaluminum compound (B-1) was used, a slurry of the solid catalyst component (X-15) obtained in Preparation Example 15 was used instead of the solid catalyst component (X-1), and the amount of the carbon material (A) solid content listed in Table 2 was charged into the reactor. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80°C for 10 hours, to obtain the amount of olefin polymer shown in Table 2.
[0133] [Table 2]
[0134] It is clear that the Examples using the organoaluminum compound (B) gave larger amounts of olefin polymer than the Comparative Examples not using the organoaluminum compound (B).
[0135] <Example 12> In a nitrogen atmosphere, 500 milliliters of heptane was added to a SUS autoclave reactor with a capacity of 1 liter, which had been thoroughly substituted with nitrogen, and ethylene was then passed through to saturate the reactor with ethylene. Next, 0.375 mL of a decane solution of the organoaluminum compound (B-1) (0.375 mmol in terms of organoaluminum compound (B-1)) and an amount of slurry equivalent to 30 mg of the solid content of the carbon material (A) were extracted from the slurry of the solid catalyst component (X-1) obtained in Preparation Example 1 and charged into the reactor. Then, the temperature and pressure were raised to 80°C and 0.8 MPaG with ethylene, and a polymerization reaction was carried out for 90 minutes at a rotation speed of 350 rpm. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80°C for 10 hours to obtain the amount of olefin polymer shown in Table 3. The molecular weight of the obtained olefin polymer is shown in Table 3.
[0136] <Examples 13 to 15> Polymerization reaction was carried out in the same manner as in Example 12, except that the slurries of the solid catalyst components (X-16) to (X-18) obtained in Preparation Examples 16 to 18 were used instead of the solid catalyst component (X-1), and the amount of the carbon material (A) shown in Table 3 was charged into the reactor. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80° C. for 10 hours to obtain the amount of olefin polymer shown in Table 3. The molecular weight of the obtained olefin polymer is shown in Table 3.
[0137] <Example 16> In a SUS autoclave reactor with a capacity of 1 liter, 500 milliliters of heptane was added under a nitrogen atmosphere, and ethylene was passed through to saturate the reactor with ethylene. Next, 3 mL of 1-hexene, 0.375 mL of a decane solution of the organoaluminum compound (B-1) (0.375 mmol in terms of organoaluminum compound (B-1)), and a slurry equivalent to 30 mg of the solid content of the carbon material (A) were extracted from the slurry of the solid catalyst component (X-19) obtained in Preparation Example 19 and charged into the reactor. Then, the temperature and pressure were raised to 80°C and 0.8 MPaG with ethylene, and a polymerization reaction was carried out for 90 minutes at a rotation speed of 350 rpm. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80°C for 10 hours to obtain the amount of olefin polymer shown in Table 3. The molecular weight of the obtained olefin polymer is shown in Table 3.
[0138] <Comparative Examples 5 to 6> Polymerization reaction was carried out in the same manner as in Example 12, except that the slurries of the solid catalyst components (X-20) to (X-21) obtained in Preparation Examples 20 to 21 were used instead of the solid catalyst component (X-1), and the amount of the carbon material (A) shown in Table 3 was charged into the reactor. After the reaction was completed, the contents in the reactor were filtered and dried under reduced pressure at 80° C. for 10 hours to obtain the amount of olefin polymer shown in Table 3. The molecular weight of the obtained olefin polymer is shown in Table 3.
[0139] [Table 3]
[0140] It can be seen that the examples in which the transition metal compounds (C-1) to (C-5) containing heteroatoms were used as the transition metal compounds gave more olefin polymers than the comparative examples in which the transition metal compounds (C'-6) to (C'-7) not containing heteroatoms were used.
[0141] ≪Weight average molecular weight (Mw)≫ The weight average molecular weight (Mw) of the olefin polymer was determined by gel permeation chromatography (GPC) using a Waters "Alliance GPC 2000" gel permeation chromatograph (high temperature size exclusion chromatograph) under the following operating conditions:
[0142] Analysis software: Chromatography data system Empower (Waters) Column: TSKgel GMH6-HT x 2 + TSKgel GMH6-HT x 2 (Inner diameter 7.5mm x length 30cm, Tosoh Corporation) Mobile phase: o-dichlorobenzene Detector: Differential refractometer (built into the device) Column temperature: 140°C Flow rate; 1.0mL / min Injection volume: 400μL Sampling time interval: 1 second Sample concentration: 0.15% (w / v) Molecular weight calibration: Monodisperse polystyrene (Tosoh Corporation) / molecular weight 495 to 20.6 million
Claims
1. A carbon material (A) that satisfies the following requirements (AI) and (A-II); An organoaluminum compound (B) represented by the following general formula (BI), A transition metal compound (C) represented by the following general formula (C-II): A catalyst for olefin polymerization comprising: (A-I) The oxygen atom / carbon atom molar ratio measured by X-ray photoelectron spectroscopy (XPS) is 0.018 or more and 0.400 or less; (A-II) Specific surface area in BET multipoint method is 100 m 2 / g or more 5000m 2 / g or less; R a m Al(OR b ) n H p X q ・・・(B-I) [In general formula (BI), R a and R b represents a hydrocarbon group having 1 to 15 carbon atoms, which may be the same or different from each other, X represents a halogen atom, m represents an integer of 1 to 3, n represents an integer of 0 to 2, p represents an integer of 0 to 2, q represents an integer of 0 to 2, and m+n+p+q=3. 【Chemistry 1】 [In general formula (C-II), M represents a transition metal atom of Group 4 or 5 of the periodic table, R 1 , R 2 , R 3 , R 4 , and R 5 may be the same or different and represent a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, a germanium-containing group, or a tin-containing group, two or more of which may be bonded to each other to form a ring; R 6 represents a hydrogen atom, a hydrocarbon group having from 1 to 3 carbon atoms and consisting only of primary or secondary carbon, an alkyl group having 4 or more carbon atoms, an aryl group-substituted alkyl group, a monocyclic or bicyclic cyclic hydrocarbon group, an aryl group, or a halogen atom; n is an integer of 1 to 4 that satisfies the valence of M; X is a leaving group selected from the group consisting of a hydrogen atom, a halogen atom, a hydrocarbon group, a halogen-containing group, a silicon-containing group, an oxygen-containing group, a sulfur-containing group, a nitrogen-containing group, a phosphorus-containing group, a boron-containing group, an aluminum-containing group, a conjugated diene derivative group, and a neutral ligand capable of coordinating with a lone electron pair, and when n is 2 or more, multiple Xs may be the same or different from each other and may be bonded to each other to form a ring.
2. 2. The olefin polymerization catalyst according to claim 1, wherein M in the general formula (C-II) is a transition metal atom of Group 4 of the periodic table.
3. 3. The olefin polymerization catalyst according to claim 1, wherein the molar ratio of oxygen atoms to carbon atoms in the requirement (AI) is 0.020 or more and 0.250 or less.
4. The specific surface area in the above requirement (A-II) is 150 m 2 / g or more 3000m 2 The olefin polymerization catalyst according to any one of claims 1 to 3, wherein the molecular weight of the catalyst is 1 / g or less.
5. The olefin polymerization catalyst according to any one of claims 1 to 4, wherein the carbon material (A) comprises at least one selected from the group consisting of carbon nanotubes, graphene, fullerene, graphite, and activated carbon.
6. A process for producing an olefin polymer, comprising a step of polymerizing an olefin in the presence of the olefin polymerization catalyst according to any one of claims 1 to 5.
7. The method for producing an olefin polymer according to claim 6, wherein the step of polymerizing an olefin is a step of homopolymerizing ethylene or a step of copolymerizing ethylene with a linear or branched α-olefin having 3 to 30 carbon atoms.
Citation Information
Patent Citations
Polyolefin catalyst adopting carbon nanotubes as carriers and preparation method thereof
CN102731693B
Metal complex composition and use of metal complex composition as catalyst for polydiene production
JP2005506404A
Polymerization catalyst, polymer obtained by using the same, and its polymer complex
JP2006176601A
Carbon nanotube-polyolefin composite
JP2007161741A
Method for producing carbon nanotube / polymer mixtures by gas-phase polymerization
JP2009545639A
